Boosting thermoelectric performance of p-type SiGe alloys through in-situ metallic YSi2 nanoinclusions. (September 2016) - Ahmad, Sajid; Singh, Ajay; Bohra, Anil; Basu, Ranita; Bhattacharya, Shovit; Bhatt, Ranu; Meshram, K.N.; Roy, Mainak; Sarkar, Shaibal K.; Hayakawa, Y.; Debnath, A.K.; Aswal, D.K.; et al.
Abstract: Incorporation of metallic yttrium silicide nanoparticles in p-type SiGe alloys matrix is demonstrated to enhance their thermoelectric performance. In this work, we report a thermoelectric figure-of-merit ( ZT ) of 1.81 (at 1100 K) in p-type SiGe alloys (that is 34% higher as compared to earlier best reported ZT value) by intentional incorporation of metallic yttrium silicide (YSi2 ) nano-inclusions. The YSi2 nanoinclusions were in-situ formed in p-type SiGe matrix by its reaction with Y2 O3 nanoparticles (≤6 wt%) during vacuum hot pressing at 1423 K under a pressure of 50 kg/cm 2 . YSi2 nanoinclusions form coherent interfaces with SiGe matrix and facilitate a reduction in the grain size of SiGe. These factors cause a strong suppression of thermal conductivity (κSiGe 3.86 Wm −1 K −1 and κSiGe-YSi2 2.38 W m −1 K −1 at 1100 K) without affecting the power factor, and therefore, results in a dramatic enhancement of ZT . In addition, SiGe-YSi2 nanocomposites exhibit enhancement in mechanical hardness, enhanced average ZT as well as compatibility factor, which are additional useful characteristics for practical applications. Graphical abstract: The coherent interface between metallic YSi2 nano-inclusions and p-type SiGe matrix result in lowering of thermal conductivity without affecting the power factor, resulting in record figure- of -merit of 1.81 at 1100 K. Highlights: Sintering of p-type SiGe with Y2 O3 results in in-situ formation of YSi2 nano-inclusions. YSi2 - SiGe coherent interface reduces thermal conductivity without affecting power factor. SiGe with YSi2 nano-inclusions exhibit figure-of-merit ( ZT ) of 1.81 (at 1100 K).